2014
DOI: 10.1155/2014/823492
|View full text |Cite
|
Sign up to set email alerts
|

Marked Antigiardial Activity ofYucca baccataExtracts: A Potential Natural Alternative for Treating Protozoan Infections

Abstract: Human Giardiosis is a public health problem in Mexico, where the national prevalence was estimated to be up to 68%. Misuse of antiprotozoal drugs may result in low effectiveness and undesirable side effects. Research on natural products is a good strategy for discovering more effective antiparasitic compounds. This study evaluated the antigiardial activity of extracts of Yucca baccata, which is native to northwestern Mexico. Forty-two gerbils (females) were weighed and orally inoculated with 5 × 106 Giardia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Several studies have been conducted to evaluate antiparasitic properties of plant extracts against Giardia intestinalis ; Ponce-Macotela et al in 2006 [ 22 ] studied the effect of oregano (Lippia berlandieri) ethanolic extracts against Giardia trophozoites at concentrations ranging from 58 to 588 μ g and demonstrated ultra-structural lesion in trophozoites, losing shape, size, and damage to the nucleus. Similar studies have been reported to different natural extracts of plants; Yucca baccata exhibited effective antigiardial activity in the proximal segment similar to metronidazole [ 23 ]. The dichloromethane fraction of peppermint presented antigiardial activity in vitro with an IC(50) of 0.75 μ g/mL causing several alterations on plasma membrane surface of the parasite and inhibited the adhesion of G. intestinalis trophozoites [ 24 ], while another study concluded that water soluble extracts of blueberries can kill G. intestinalis trophozoites and modify the cell morphology [ 25 ].…”
Section: Resultssupporting
confidence: 79%
“…Several studies have been conducted to evaluate antiparasitic properties of plant extracts against Giardia intestinalis ; Ponce-Macotela et al in 2006 [ 22 ] studied the effect of oregano (Lippia berlandieri) ethanolic extracts against Giardia trophozoites at concentrations ranging from 58 to 588 μ g and demonstrated ultra-structural lesion in trophozoites, losing shape, size, and damage to the nucleus. Similar studies have been reported to different natural extracts of plants; Yucca baccata exhibited effective antigiardial activity in the proximal segment similar to metronidazole [ 23 ]. The dichloromethane fraction of peppermint presented antigiardial activity in vitro with an IC(50) of 0.75 μ g/mL causing several alterations on plasma membrane surface of the parasite and inhibited the adhesion of G. intestinalis trophozoites [ 24 ], while another study concluded that water soluble extracts of blueberries can kill G. intestinalis trophozoites and modify the cell morphology [ 25 ].…”
Section: Resultssupporting
confidence: 79%
“… 2006 ( Moon et al, 2006 1 ) Yucca baccata Asparagaceae Stem Aqueous extract Mexico 24.4, 12.2, and 6.1 mg/mL/day for 3 days In vivo (Mongolian gerbils) Trophozoites Yucca extracts reduced, albeit not significantly, the trophozoite counts in the duodenum segment. Only the high-extract concentration significantly reduced the trophozoite counts in the proximal segment and it was similar to that of metronidazole 2014 ( Quihui-Cota et al, 2014 ) Zingiber officinale Zingiberaceae Rhizome dichloromethane extracts Egypt 10 and 20 mg/kg/day In vivo ( Balb/c mice ) Cyst The administration of ginger especially at the dose 20 mg/kg/day significantly reduced the excretion rates of dead cysts and intestinal trophozoite (100%) in the faeces of the treated groups similar to that of the 20 mg/kg/day MTZ treatment. 2016 ( Dyab et al, 2016 ) …”
Section: Resultsmentioning
confidence: 59%
“…Yucca schidigera is one of the species extensively investigated on its antimicrobial properties [ 14 ]. In addition, Yucca baccata ( Y. baccata ), endemic to Northwestern Mexico, seems to have a high concentration of saponins [ 15 ]. However, information about its antimicrobial activity or antioxidant capacity remains limited; therefore, the goal of this work was to provide evidence of the antioxidant and antibacterial activity of Y. baccata .…”
Section: Introductionmentioning
confidence: 99%